Repetitive trigeminal nociceptive stimulation in rats increases their susceptibility to cortical spreading depression. (May 2016) - Toriumi, Haruki; Shimizu, Toshihiko; Ebine, Taeko; Takizawa, Tsubasa; Kayama, Yohei; Koh, Anri; Shibata, Mamoru; Suzuki, Norihiro
Highlights: Cortical spreading depression (CSD) is known to be related to migraines. We explored the threshold change to evoke CSD by nociceptive stimulation. Trigeminal nociceptive stimulation lowered the threshold to induce CSD. Administration of a GABAA receptor agonist decreased these effects. Trigeminal nociceptive stimulation may affect the exacerbation of migraines. Abstract: We examined the ability of trigeminal nerve activation to induce cortical spreading depression in rats. Capsaicin was injected into the bilateral plantar or whisker pad for either 4 or 6 days in rats. The number and duration of cortical spreading depressions induced by potassium were significantly increased in animals injected with capsaicin in the bilateral whisker pad compared with animals injected in the bilateral plantar or in controls, while administration of a GABAA receptor agonist decreased these effects. Repetitive nociceptive stimulation of the trigeminal nerve lowers the threshold for the induction of cortical spreading depression by altering GABAergic neuronal activity.